Staphylococcus aureus at an Indian tertiary hospital: Antimicrobial susceptibility and minimum inhibitory concentration (MIC) creep of antimicrobial agents. (June 2019) - Khurana, Surbhi; Mathur, Purva; Malhotra, Rajesh
Highlights: Changing vancomycin, linezolid and rifampicin MICs in susceptible S. aureus, towards reduced susceptibility. Statistically significant decrease in MIC50 of rifampicin. Rifampicin and teicoplanin MIC creep was observed, but not for vancomycin or linezolid. MIC creep is indicative that even susceptible S. aureus are not inert to antibiotic pressure. A multidisciplinary approach and preventive measures are required to address the challenge of emerging MIC creep. Abstract: Objectives: Staphylococcus aureus causes a variety of symptoms and diseases and has been associated with high morbidity and mortality. A global population drift in clinical S. aureus isolates towards reduced antimicrobial susceptibility is being reported. In this study, the antimicrobial susceptibility profile and minimum inhibitory concentration (MIC) creep of vancomycin, linezolid, teicoplanin and rifampicin against clinical S. aureus isolates at an Indian tertiary centre from January 2012 to December 2016 were investigated. Methods: All consecutive, non-duplicate S. aureus isolates ( n = 1466) recovered from hospitalised patients identified by VITEK ® 2 were included in the study. Clinical isolates were tested against 20 antibiotics and were evaluated according to Clinical and Laboratory Standards Institute (CLSI) guidelines. Statistical significance of the MIC creeps of four antimicrobials (vancomycin, linezolid, teicoplanin and rifampicin) was ascertained. Results: S. aureus isolates recovered from all clinical samples demonstrated high resistance to ampicillin, ciprofloxacin and penicillin (75–100%) and low resistance to amikacin, linezolid, netilmicin, nitrofurantoin, teicoplanin and vancomycin (0–13%). The MIC90 values (MIC required to inhibit 90% of the isolates) for vancomycin, linezolid and rifampicin decreased, whereas the MIC90 for teicoplanin increased. The change in the geometric mean MIC of rifampicin was found to be statistically significant. A statistically significant and progressive MIC creep was observed for teicoplanin and rifampicin. Conclusion: Despite remaining susceptible, S. aureus is not inert to antibiotic pressure. Implementation of preventive measures in healthcare settings is required worldwide to combat the increasing number of infections by this pathogen.